Association of cigarette and electronic nicotine delivery systems use with internalizing and externalizing problems among US adults: Findings from wave 3 (2015-2016) of the PATH study. - Bekir Kaplan (Public Library of Science (PLoS), 2021)
Aims Electronic Nicotine Delivery System (ENDS) use is increasing among US adults. While existing research has demonstrated higher cigarette smoking rates among people with mental health conditions, there is sparse information on the association between ENDS use and mental health such as internalizing and externalizing problems. The aim of this study was to evaluate associations between internalizing and externalizing problems for cigarette only, ENDS only, and dual users, as well as changes in mental health among those groups. Method We used the U.S. Population Assessment of Tobacco and Health (PATH) Study Wave 3 adult data. Internalizing and externalizing problems were self-reported and assessed via the Global Appraisal of Individual Needs-Short Screener; response options were dichotomized to reflect past 12 months and any lifetime problems. Self-reported changes in mental health over the past 12 months were also assessed. Participants' tobacco use status was categorized as ENDS only use (n = 618), cigarette only use (n = 6,779), dual use (cigarettes and ENDS) (n = 681), and non-current use (n = 16,515). Results Lifetime and past 12 month internalizing problems were reported by 63.8% (n = 18,706) and 50.4% (n = 15,326), respectively, while lifetime and past 12 months externalizing problems were reported by 63.3% (n = 18,835) and 52.7% (n = 16,005), respectively. Six percent of participants reported worse mental health over the past 12 months. Compared to non-current use of any tobacco product, and adjusting for age, sex, race, education, and household income, those reporting ENDS use only had higher odds of ever (aOR = 1.52; 95%CI: 1.22-1.89) and past 12 months (aOR = 1.49; 95%CI: 1.22-1.84) internalizing, and externalizing problems (aOR = 1.32; 95%CI: 1.04-1.66 and aOR = 1.34; 95%CI: 1.07-1.67, respectively), and higher odds of reporting worse mental health over the past 12 months (aOR = 1.50; 95%CI: 1.05-2.12). Conclusion Health care providers should be aware that internalizing and externalizing problems, and worsening mental health, are more common among adults who use ENDS, cigarettes, or both of these tobacco products.